EDUCATION AND TRAINING THROUGH MINIMOVIE MEDIA AS A PREVENTION OF SEXUAL VIOLENCE IN SCHOOL AGE CHILDREN - Iqlima Dwi Kurnia; Ilya Krisnana; Praba Diyan Rachmawati; Yuni Sufyanti Arief; Farida Norma Yuliati (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2021)
Introduction: Cases of violence against children in Indonesia have a high number. Particularly the sexual abuse against children which has increased in the society. Lack of sexual education in children can affect the child’s emotional maturity and knowledge in assessing the deviates situation in surrounding environment. As a consequence, the child could not find ways in handling the violence behaviour. The Aim of this community services were to increase emotional maturity and knowledge about prevention of sexual violence.Methods: The activities used in this community service program are in the form of education and training using minimovie media at PPTQKids Darul Quran Surabaya for 30 elementary students of grade 1 and 2. The Topic of education about types of sexual violence against children, methods of prevention, what to do if a foreigner commits sexual violence.Results: Darul Quran PPTQKids students who take part in community service activities are very enthusiastic, both for day 1 related to providing information through minimovie and day 2 when providing training with the demonstration method. The results of the post-test showed that some respondents had a high level of knowledge as many as 27 students (90%). 22 respondents had a high level of emotional maturity (73.33%).Conclusion: Community service activities through minimovie media with education and training can increase knowledge and emotional maturity as an effort to prevent sexual violence. Minimovie media can be applied as one of the effective media in providing health education for school-age children.